Select targeting of intracellular Toll-interleukin-1 receptor resistance domains for protection against influenza-induced disease. Issue 1 (January 2020) - Shirey, Kari Ann; Lai, Wendy; Brown, Lindsey J; Blanco, Jorge C G; Beadenkopf, Robert; Wang, Yajing; Vogel, Stefanie N; Snyder, Greg A
TLRs are a family of PRRs that respond to PAMPs or host-derived Danger-Associated Molecular Patterns (DAMPs) to initiate host inflammation and immune responses. TLR dimerization and recruitment of adapter molecules is critical for intracellular signaling and is mediated through intracellular Toll-Interleukin 1 Receptor Resistance (TIR) domain interactions. Human TIR domains, including reported structures of TIR1, TIR2, TIR6, TIR10, TIRAP, and MyD88, contain Cysteine (Cys) interactions or modifications that are disproportionally at, or near, reported biological TIR interfaces, or in close proximity to functionally important regions. Therefore, we hypothesized that intracellular TIR Cys regulation may have greater functional importance than previously appreciated. Expression of mutant TLR4-C747S or treatment of TLR4 reporter cells with a small molecule, Cys-binding inhibitor of TLR4, TAK-242, abrogated LPS signaling in vitro . Using TAK-242, mice were protected from lethal influenza challenge as previously reported for extracellular TLR4 antagonists. Molecular modeling and sequence analysis of the region surrounding TLR4-Cys747 indicate conservation of a WxxxE motif identified among bacterial and NAD + -consuming TIRs, as well as within the TIRs domains of surface TLRs 1, 2, 4, 6, and 10. Together, these data support the hypothesis that critical Cys within the TIR domain are essential for TLR4 functionality.